RETRACTED: Pro-inflammatory Effect of Downregulated CD73 Expression in EAE Astrocytes - Zhou, Shumin; Liu, Guoping; Guo, Jie; Kong, Fanqiang; Chen, Song; Wang, Zhiyun (Frontiers in Cellular Neuroscience, 2019)
Abstract: CD73, an ectonucleotidase, participates in the regulation of immune responses by controlling the conversion of extracellular AMP to adenosine. In this study, we investigated whether any type of neural cells, especially neuroglia cells, exhibit altered CD73 expression, localization or activity upon experimental autoimmune uveitis (EAE) induction and whether altered CD73 manipulates the activation of effector T cells that interact with such cell types. First, the amount of cell membrane-exposed CD73 was detected by flow cytometry in various types of neural cells collected from either naïve or EAE mice. Compared to that in astrocytes from naïve control mice, the amount of membrane-bound CD73 was significantly decreased in astrocytes from EAE mice, while no significant differences were detected in other cell types. Thereafter, wild-type and CD73-/- astrocytes were used to study whether CD73 influences the function of inflammatory astrocytes, such as the production of cytokines/chemokines and the activation of effector T cells that interact with astrocytes. The results indicated that the addition of exogenous AMP significantly inhibited cytokine/chemokine production by wild type astrocytes but had no effect on CD73-/- astrocytes and that the effect of AMP effect was almost completely blocked by the addition of either a CD73 inhibitor (APCP) or an adenosine receptor A1 subtype (ARA1) antagonist (SLV320). Although the addition of AMP did not affect CD73-/- astrocytes, the addition of adenosine successfully inhibited their cytokine/chemokine production. The antigen-specific interaction of astrocytes with invading CD4 cells caused CD73 downregulation in astrocytes from mice that underwent EAE induction. Collectively, our findings support the conclusion that, upon EAE induction, likely due to an interaction with invading CD4+ cells, astrocytes lose most of their membrane-localized CD73; this inhibits the generation of adenosine in the local microenvironment. As adenosine has anti-inflammatory effects on astrocytes and CNS-infiltrating effector T cells in EAE, the downregulation of CD73 in astrocytes may be considered a pro-inflammatory process for facilitating the pathogenesis of EAE.